Kepemimpinan Transformasional di Lembaga Pendidikan Islam: Transformational Leadership in Islamic Educational Institutions - Nahdiyah KY, Nuurun; Maunah, Binti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
Changes in times move so fast, all lines of life are required to be able to move with the flow of time. Change demands that all lines of life, including the educational space, can answer the complexity of the problems that arise from the effects of change. This paper focuses on discussing the definition of transformational leadership in Islamic educational institutions, and the implementation of transformational leadership in Islamic educational institutions. the method used is to use a literature review, by taking an inventory of the literature that has the same data needed, and then an analysis is carried out by correlating several educational institutions that are the focus of case analysis. The results of these six studies show that Transformational Leadership is implemented in Islamic education institutions, both in Islamic boarding schools and madrasas, and provides significant results in efforts to improve the quality of education. Implementation efforts carried out in five educational institutions have the same pattern, it is proven that Islamic educational institutions that implement leadership actualize the four main dimensions of transformational leadership. This has been proven to have been carried out at MI Maarif NU Pageruji, the heads of MTsN throughout the city of Kediri, MTsN 2 Medan, MTsN South Jakarta, and MI Maarif Depok Sleman. While one leadership has a different characteristic, namely the transformational leadership of the kyai in the pesantren, this is different from the other five institutions, because the Kyai in the pesantren has an inherent charisma, which the other five leaderships do not have.